Peran Toba Dreams Dalam Pengembangan Destinasi Wisata Danau Toba: Pendekatan Sastra Pariwisata - Simanihuruk, Bertova; Surbakti, Asmyta; I Nyoman Darma Putra; Eddy Setia (Program Studi Pendidikan Bahasa dan Sastra Indonesia FKIP Universitas Islam Riau, 2022)
North Sumatra literary works have represented Lake Toba tourism phenomena in the form of natural beauty, culture, and local wisdom. However, these works still need to get more attention from any researchers who link them to another way of promoting tourism. This study aims to analyze the four tourism components in Toba Dreams' novel and the role of the novel in developing Lake Toba's tourist destination. This study used a qualitative-interpretative method with a phenomenological paradigm. In obtaining the primary data, we used text, and in collecting the secondary data, we took from the library, observation, and interview methods. All primary data, i.e., attractions, amenities, access, and ancillary services, are analyzed using mimetic and literary tourism approaches by comparing them with secondary data acquisition. The results of this study show that the novel intensely and aesthetically depicts four tourism components, imitations of reality. The novelty of this study is that the Toba Dreams novel has a dual function as a medium for stories and as a promotion of Lake Toba tourism, especially tourist destinations in the